Secondary postpartum hemorrhage after pineapple juice- a case report - Thomas, Charisma Rebecca; Nair, Sobha S.; Puthenveettil, Nitu; Sudhakar, Namita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Postpartum hemorrhage (PPH) is defined as blood loss through the genital tract, exceeding 500 mL following vaginal birth and 1000 mL following caesarean section. PPH occurring between 24 hours to 12 weeks postpartum is defined as secondary PPH. PPH is the most common preventable cause of maternal morbidity and mortality. Detailed history and careful clinical examination can help in proper diagnosis. This is a case report of consumption of pineapple juice, that caused secondary PPH. Bromelain in pineapple juice is known to have proteolytic, fibrinolytic, anti-inflammatory and antithrombotic properties. It causes moderate prolongation of activated partial thromboplastin time (APTT), thus delaying coagulation. This action of bromelain was found to be concentration dependent. Prompt activation of the transfusion protocol can be lifesaving. Coagulation parameters should be monitored and respective blood products should be given. Thromboelastogram (TEG)/ Rotational Thromboelastometry (ROTEM) can be used for the same. To conclude, a multi-disciplinary approach is ideal. Mechanical and medical management of PPH should be started simultaneously. This should be followed by surgical procedures. If interventional radiology procedures like uterine artery embolization are available, they can be utilised, without risking the life of the mother.